Integrating Business Improvement and Innovation Models: a Step Change Approach for Organisational Performance Improvement - Al-Tameemi, Khaldoon; Alshawi, Mustafa; Ahmed, Vian (International Journal of Engineering and Technology, 2018)
The purpose of this paper is to propose an alternative approach to guide public sector organisations, in the developing world, to quickly create an effective work environment to attract Multinational Corporation (MNCs) to foster Foreign Direct Investment (FDI) inflows to deliver their large and strategic investment Projects. The paper provides extensive literature review to discuss the need for public sector performance improvement, in the developing world, and its impact on attracting MNCs and fostering Foreign Direct Investment (FDI) as well as understanding the existing performance methodologies that can help such organisations improvement their performance. The paper, then proposes an alternative to the existing performance improvement methodologies that is capable of introducing a step change to the performance of public sector organisations in a relatively shorter period of time to enable developing world countries to attract MNCs to deliver their strategic projects. A multiple case study research strategy was selected to validate the proposed approach. The findings have confirmed the effectiveness and appropriateness of the proposed approach for overcoming existing weaknesses in the performance of public sector organisations in a relatively shorter period of time. The proposed approach addresses the weakness of the existing performance improvement methodologies to overcome the time factor required for public sector originations to introduce significant performance improvement to attract FDI projects. It can serve as an alternative management structure that is specifically developed to emulate world-class performance in a short period of time without the need to get into the complications of using existing performance improvement methodologies for such organisations, which is rather complicated, lengthy and highly risky.